THE INTERSECTION OF QURAN AND SCIENCE: ANALYZING THE METHODOLOGIES OF TWO CONTEMPORARY EXEGETES - Dr. Rizwan Haider; Dr. Abdul Wahid; Dr. Adnan Shahzad (Review Journal of Social Psychology & Social Works, 2024)
Tafseer, the interpretation of the Quran, has been a fundamental aspect of Islamic scholarship for centuries, serving as the primary means through which the meanings of the Quranic text are elucidated. In modern times, the intersection between Tafseer and scientific knowledge has given rise to a distinct approach known as scientific Tafseer, which seeks to reconcile Quranic revelations with contemporary scientific discoveries, leading to diverse interpretations by scholars. This article presents a comparative analysis of the scientific Tafseer methodologies employed by two prominent contemporary exegetes: Dr. Israr Ahmed and Shaykh Mutawalli Ash-Sharawi. Both have made significant contributions to the field of scientific Tafseer, yet their approaches reflect distinct perspectives on the relationship between modern science and the Quranic text. Dr. Israr Ahmed integrates scientific knowledge cautiously, emphasizing the Quran’s primacy over empirical science, ensuring that scientific findings serve as tools to illustrate Quranic truths, without being a measure of their validity. Conversely, Shaykh Mutawalli Ash-Sharawi adopts a more critical stance, frequently warning against an over-reliance on scientific theories when interpreting Quranic verses, and focusing on the metaphysical dimensions of the Quran, critiquing the limitations of human knowledge in fully understanding divine wisdom. By analyzing key Tafseer works from both scholars, this article highlights their distinct methodologies, shedding light on the broader implications for the role of science in contemporary Islamic thought, while also exploring the strengths and challenges of integrating modern science into Quranic interpretation and offering insights into the future trajectory of scientific Tafseer. Keywords: Tafseer, Scientific Tafseer, Dr. Israr Ahmed, Shaykh Mutawalli Ash-Sharawi, Science and Revelation, Comparative analysis, Islamic scholarship, Modern science and Quran, Methodology of exegesis.